Elaboración de un documental sobre la evolución del hip hop en Quito-Ecuador - Terán Barahona, Christian Patricio (2020)
Hip Hop is one of the urban cultures with the most followers around the world at present, it is made up of four artistic elements which are, graffiti, which is the deformation of letters and sometimes they are accompanied by characters such as caricatures or portraits , the breakdance that is basically the dance, the djs are the people in charge of the musical production and of creating the rhythm, and the mcs are the ones that compose the lyrics to obtain as the final product the music better known as Rap. Hip Hop was born in New York City as a form of protest against racism and social inequality that affected part of the New York population in the mid-1970s. Ecuador is one of the countries that has adapted this urban culture in the 80s, a time when it was not accepted by society, because it was associated with crime. Either way, young people wanted to express their art, therefore, they educated themselves to improve their technique, resulting in national and international recognition, becoming references of Rap music today. From there Hip Hop arrives in Quito, a city where several groups are created that represent this culture in an extraordinary way, since their work is recognized in several countries and Ecuador begins to have notoriety in Latin Hip Hop, therefore, artists have a need to progress, which forces them to improve their art. Since then, Hip Hop has been constantly evolving, with technology being a fundamental piece for new generations, which have tutorials and other tools available to learn about Hip Hop culture and techniques that help its production, so that finally they can spread their works through the internet.